OPTIMIZATION OF THE MEDICAL ABORTION THROUGH QUESTIONNAIRES AND THE USE OF A LOW-SENSITIVITY PREGNANCY TEST DURING THE COVID-19 PANDEMIC - Daniyarov A.A; Gadoeva D.A; Sagdullaeva U.A; Sidikxodjaeva M.A (Scholar Express Journals, 2024)
Despite a number of studies conducted in recent years, abortion still remains a hot topic. Today, several types of contraceptive methods are available, but even they cannot completely eliminate the incidence of unwanted pregnancy [1]. According to recent statistics, 72% of women have had an abortion once in their lives, but the impact of this history on the course of pregnancy and its complications was not taken into account when planning future pregnancies [2]. In this article we provided the results of our research that were collected during a medical abortion at home
Keywords: abortion; complications of abortion; family planning; medical abortion